2017
DOI: 10.1038/s41598-017-04237-z
|View full text |Cite
|
Sign up to set email alerts
|

Metal vapor micro-jet controls material redistribution in laser powder bed fusion additive manufacturing

Abstract: The results of detailed experiments and finite element modeling of metal micro-droplet motion associated with metal additive manufacturing (AM) processes are presented. Ultra high speed imaging of melt pool dynamics reveals that the dominant mechanism leading to micro-droplet ejection in a laser powder bed fusion AM is not from laser induced recoil pressure as is widely believed and found in laser welding processes, but rather from vapor driven entrainment of micro-particles by an ambient gas flow. The physics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
189
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 383 publications
(207 citation statements)
references
References 36 publications
17
189
1
Order By: Relevance
“…13,14 Although the laser irradiates on the melt pool (liquid) and not on the powder bed during the SLM process, 15 the effective optical absorption could have improved due to the continuous incorporation of the oxidized copper powder particles from the denudation zone into the melt pool, offering a fresh and optically absorptive powder surface. 15,16 Figure 2A shows the evolution of the relative density of the parts as a function of the applied volumetric energy density for different input power levels in an argon and nitrogen atmosphere. It is clear that a laser power of 300 and 400 W is not sufficient to cause full melting of the copper powder, resulting in lower relative part density (below 93%).…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Although the laser irradiates on the melt pool (liquid) and not on the powder bed during the SLM process, 15 the effective optical absorption could have improved due to the continuous incorporation of the oxidized copper powder particles from the denudation zone into the melt pool, offering a fresh and optically absorptive powder surface. 15,16 Figure 2A shows the evolution of the relative density of the parts as a function of the applied volumetric energy density for different input power levels in an argon and nitrogen atmosphere. It is clear that a laser power of 300 and 400 W is not sufficient to cause full melting of the copper powder, resulting in lower relative part density (below 93%).…”
Section: Methodsmentioning
confidence: 99%
“…During LPBF, it is very common to see very bright ejections (sparks) leaving the laser-powder interaction area; the melt pool undergoes a high degree of superheat, leading to vaporization and material ejection [35,114,115]. Ly et al [35] reported recently that, while the dominant mechanism of denudation is vapor recoil pressure, the formation of ejections is mostly influenced by vapor-driven entrainment of micro-particles.…”
Section: Heat-affected Powdermentioning
confidence: 99%
“…The interaction between the high-energy laser typical of LPBF equipment and the metal powder bed can result in powder contamination through different phenomena including agglomeration, partial fusing, partial/full oxidation, metal vapor condensate, and generation of spatter [32][33][34][35][36][37][38][39][40]. These phenomena can alter not only the properties of the reused powder (i.e., flowability, chemical composition, tap density, particle size), but also the surface (i.e., roughness), microstructural (i.e., local variation of chemical composition, pore formation), and mechanical properties of the final part.…”
Section: Introductionmentioning
confidence: 99%
“…For these melt pool models, an appropriate powder-bed model should be employed. Modeling of the powder-bed has been done in two different ways: powder-scale (refer to [28][29][30][31][32][33][34][35]) and continuum-scale (refer to [36][37][38][39][40][41][42][43]). Although the first approach enables simulating the size variations and the local changes in the melt pool such as incomplete melting or formation of pores [28,29], it is computationally expensive such that it is almost impossible to use it for full-part simulation.…”
Section: Melt Pool Modeling Through Fem Based Thermal Modelingmentioning
confidence: 99%